Low health literacy and cancer screening among Chinese Americans in California: a cross-sectional analysis. Issue 1 (5th January 2015) - Sentell, Tetine L; Tsoh, Janice Y; Davis, Terry; Davis, James; Braun, Kathryn L
Abstract : Objectives: Cancer is the leading cause of death among Asian Americans. Chinese Americans comprise the largest Asian American ethnic group. Low health literacy (LHL) is associated with lower cancer screening rates, but this association has not been studied in Chinese Americans. We examined the relationship between LHL and meeting US Preventive Service Task Force (USPSTF) guidelines for cervical, colorectal and breast cancer screening among Chinese Americans. Design: Observational study of Chinese respondents in the 2007 California Health Interview Survey, a population-based survey. Interview languages included English, Cantonese and Mandarin. Setting: California, USA Participants: Chinese respondents in age/gender groupings appropriate for USPSTF cancer screening guidelines ( cervical : women ages 21–65, n=632; colorectal : men or women ages 50–75, n=488; and breast : women ages 50–74, n=326). Outcomes: Relationships were tested using multivariable logistic regression models controlling for healthcare access and demographic factors, including limited English proficiency (LEP). The combined effects of having both LHL and LEP were specifically examined. LHL was measured by 2-items on perceived ease-of-use of written medical materials. All study variables were self-reported. Results: Cancer screening percentages among Chinese Americans were 77.8% for cervical, 50.9% for colorectal (47.9% for women and 54.2% for men), and 85.5% for breast. LHL was associated with lower odds of meeting breast cancer screening guidelines (OR 0.41; 95% CI 0.20 to 0.82). Respondents with both LHL and LEP were significantly less likely to have up-to-date colorectal (OR 0.49; 95% CI 0.25 to 0.97) and breast cancer screening (OR 0.21; 95% CI 0.08 to 0.54) than those with neither health communication barrier. In all multivariable models, having seen a physician in the past year was a significant predictor of an up-to-date screening. Conclusions: In Chinese Americans, LHL and LEP were negatively associated with up-to-date breast and colorectal cancer screening, independent of a recent physician visit. Efforts to promote cancer screening among Chinese Americans should consider and address LHL, LEP and physician access barriers.